Intranasal delivery of Paclitaxel encapsulated nanoparticles for brain injury due to Glioblastoma. (December 2020) - Zhang, Ying; Sun, Chao; Zhang, Qingtao; Deng, Yongbing; Hu, Xi; Chen, Peng
Brain injury is a common cause for physical and emotional effects to the large number of populations. Moreover, glioblastoma is the tumor in brain with no possible treatment leading to death. The blood–brain barrier's makes the treatment more difficult by preventing the drugs to reach central nervous system. Paclitaxel (PTX) encapsulated Poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NPs), PTX-PLGA-NPs were developed using emulsification method. The PTX-PLGA-NPs were characterized using Malvern Zetasizer and Scanning Electron Microscopy and were evaluated for their cytotoxicity in U87MG cells. PTX-PLGA-NPs were prepared using single emulsion method having size of 154 ± 22.19 nm with zeta potential of –23.7 mV. The PTX-PLGA-NPs were spherical in shape and have dose dependent cytotoxicity on U87MG cells. The PTX was released from the particles with initial burst release followed by sustained release pattern. The biodistribution was studied in mice with glioblastoma model using 125 I radiolabeled PTX-PLGA-NPs and anti-glioblastoma was studied with PTX-PLGA-NPs. The biodistribution studies revealed PTX-PLGA-NPs after intranasal administration resulted in higher in vivo uptake with high anti-glioblastoma efficacy. The results suggest that PTX-PLGA-NPs administered through intranasal route have potential in the treatment of glioblastoma.